Invariant Points and 𝜀-Simultaneous Approximation - Sumit Chandok; T. D. Narang (International Journal of Mathematics and Mathematical Sciences)
We generalize and extend Brosowski-Meinardus type results on invariant points from the set of best approximation to the set of 𝜀-simultaneous approximation. As a consequence some results on 𝜀-approximation and best approximation are also deduced. The results proved in this paper generalize and extend some of the known results on the subject.